Valence States in CeVO4 and Ce0.5Bi0.5VO4 Probed by Density Functional Theory Calculations and X-ray Photoemission Spectroscopy - WATSON, GRAEME (My University, 2014)
Ce is one of the few lanthanide elements to exhibit well-defined (III) and (IV) oxidation states in solid state environments and there is therefore ambiguity as to whether CeVO4 should be formulated as Ce(III)V(V)O4 or Ce(IV)V(IV)O4. To address this question CeVO4 and Ce0.5Bi0.5VO4 have been studied by density functional theory calculations and X-ray photoemission spectroscopy. A peak above the main O 2p valence band in photoemission is attributed to localised Ce 4f states, in agreement with the calculations which show occupation of Ce 4f states. The Ce 3d core level spectrum is diagnostic of Ce(III) with no sign of a peak associated with 4f0 final states that are characteristic of Ce(IV) compounds. The experimental and theoretical results thus confirm that both compounds contain Ce(III) and V(V), rather than Ce(IV) and V(IV). In agreement with experiment, the calculations also show that the tetragonal zircon phase adopted by CeVO4 is more stable for Ce0.5Bi0.5VO4 than the monoclinic clinobisvanite phase adopted by BiVO4, so that formation of the stereochemically active Bi(III) lone pairs is suppressed by Ce doping.
PUBLISHED
Keywords: Ce doping; Ce doping